The Challenge of Implementing The Merdeka Campus Program Policy In The Covid-19 Pandemic Period - Yulia Della Paramitha; Prita Veronica Putri Oktaviana; Salsabila Azzahra Fauzia; Kismartini Kismartini; Agustin Rina Herawati (Ridwan Institute, 2021)
Education in the 4.0 revolution era is an innovation (student centered) to strengthen creativity and mentality in facing challenges. The challenges during the Covid-19 pandemic require education to use technology assistance. Therefore, the Minister of Education and Culture, Nadiem Makarim, established the Merdeka Campus program policy as a strategic plan for the development of national education. In an effort to implement the Merdeka Campus program, of course, there are challenges during the Covid-19 pandemic. The method used in writing this article is a qualitative approach with the library method. Therefore, the author wants to examine more deeply about the analysis of the challenges of implementing the Merdeka Campus program policy during the Covid-19 pandemic